Literature Review: Pengaruh Pemberian Aromaterapi Sebagai Intervensi Asuhan Keperawatan Terhadap Tingkat Kecemasan Pada Lansia - Eriyono Budi Wijoyo (Jurnal Kesehatan Rajawali, 2021)
Introduction : The aging process is a process marked by a decrease or change in various physical, psychological and social conditions in interacting with other people. Of the various elderly who experience physical changes will affect health and will cause a decrease in welfare so that it can cause psychological problems, one of which is anxiety. Elderly who experience psychological problems such as anxiety, then these conditions can interfere with the daily activities of the elderly. One of the non-pharmacological therapies to reduce anxiety levels that is easy to do and affordable is Aromatherapy. Objective: To determine the effectiveness of aromatherapy in reducing anxiety levels in the elderly based on the Literature Review. Methods: Search articles using PubMed, Google Scholar and World Wide Science, then found 8 articles according to the inclusion and exclusion criteria which were then reviewed. Results: Based on eight reviewed journals, an effective therapy to reduce anxiety levels in the elderly is by giving aromatherapy with fruit and flower essential oils. Discussion: giving aromatherapy can be done 3-7 days and there are some journals that are done for 30 days in a row and given for 10-15 minutes. Conclusion: giving aromatherapy is very effective in reducing anxiety levels in the elderly because the therapy is easy, safe, effective, non-invasive, and can be done by all ages.